Eating habits and emotional state of the population of two districts of the Tacna region, in the period of isolation the Covid – 19 - Quispe Guerra, Gaby Yamilex (2020)
The objective of the study was to determine the effects of Covid-19 isolation and its relationship to eating habits in two districts of the Tacna region in 2020, identifying the effects on food, food consumption, involuntary food search, food behavior and emotional health of the population. The methodology is non-experimental, transverse, the population studied was composed of settlers from the district of Tacna (urban area) and the district of Locumba (rural area), determining probabilistic samples of 386 and 300 respectively, between the ages of 18 to 64 years. The survey technique was used, developing an instrument with 79.4% reliability (Cronbach alpha) consisting of 19 questions that were categorized into dimensions and analyzed using non-parametric tests of Chi squared. The results indicate that changes in eating habits are related to Covid-19 isolation in the two districts with a 95% confidence level, and when comparing changes due to the pandemic in the two districts, Locumba district was found to have the greatest effects. It is therefore concluded that if there were effects caused by Covid-19 isolation on eating habits in the two districts of the Tacna region